Clean chlorination of silica surfaces by a single-site substitution approach. Issue 12 (28th February 2018) - Maity, Niladri; Barman, Samir; Abou-Hamad, Edy; D'Elia, Valerio; Basset, Jean-Marie
Abstract : Unveiling a clean, selective chlorination method for the quantitative substitution of well-defined non-hydrogen bonded silanol groups of the silica surface. Abstract : A chlorination method for the selective substitution of well-defined isolated silanol groups of the silica surface has been developed using the catalytic Appel reaction. Spectroscopic analysis, complemented by elemental microanalysis studies, reveals that a quantitative chlorination could be achieved with highly dehydroxylated silica materials that exclusively possess non-hydrogen bonded silanol groups. The employed method did not leave any carbon or phosphorus residue on the silica surface and can be regarded as a promising tool for the future functionalization of metal oxide surfaces.